A critical review of private labels (PLs): implications for managing retail brands - Molinillo-Jiménez, Sebastián (My University, 2013)
Purpose – The aim of this paper is to present a review of the state of empirical and theoretical research about Private Labels (PL) and to develop a framework for future research. Design/methodology/approach – This paper presents a bibliometric study of recent advances in the research of PL, based on citation counts; it focuses on the period of greatest scientific output (2000-2012) and consults all the international publications on marketing ranked by the Academic Journal Quality Guide. Findings – The results reveal the influence of differing topics on PL (consumer perceptions and behavior, price, channel relationships and quality). Principal contributions have been identified and areas suggested for future research (e.g. countries with diverse environments, product category, commercial formats, segmentation, brand aspects). Research limitations/implications – Future researchers could broaden the bibliographic content analysis by means of activity and relational indicators.Practical implications - The findings and the proposals for future lines of research will help retail managers to identify relevant strategies. Originality/value - This work focuses on the period of greatest output of PL academic literature and consults the main bibliographical and editorial databases. This has yielded the largest selection of articles (205) ever to be reviewed on the subject of PL. The value of the paper can be found in achieving a more profound understanding of the nature of PL for, equally, academics and industry
Keywords: Marcas registradas; Private label; Private label brand; Private brand; Store brand; Own-brand; Retail brand; Review; Methodology